1993
DOI: 10.1002/j.1556-6978.1993.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Education 2000: Extinction or Distinction?

Abstract: The supply of qualified counselor educators is diminishing in proportion to present and future demands. The authors explore historical perspectives, present concerns, and potential solutions to this growing problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…The work of Maples and her colleagues (Maples, 1989;Maples, Altekruse, & Testa, 1993;Maples & Macari, 1998) established the need for an increased pool of counselor education graduates (CEs) in the foreseeable future to fill faculty positions in counselor education programs. These predictions were further supported by Rogers et al (1998) who reported that programs accredited by the Council for Accreditation of Counseling and Related Educational Programs (CACREP) projected a need for 211 new faculty members over 10 years.…”
mentioning
confidence: 99%
“…The work of Maples and her colleagues (Maples, 1989;Maples, Altekruse, & Testa, 1993;Maples & Macari, 1998) established the need for an increased pool of counselor education graduates (CEs) in the foreseeable future to fill faculty positions in counselor education programs. These predictions were further supported by Rogers et al (1998) who reported that programs accredited by the Council for Accreditation of Counseling and Related Educational Programs (CACREP) projected a need for 211 new faculty members over 10 years.…”
mentioning
confidence: 99%
“…However, if the future survival of Counseling is indeed threatened (see Maples et al, 1993), a strong identity is important, just as Ritchie (1994) and Altekruse (1994) have said.…”
Section: 'The Quest For Identitymentioning
confidence: 94%
“…Between 1990 and 1993, Maples, Altekruse, and Testa (1993) documented an increase in the request for a school counselor specialization. The current study found this trend has continued, as did Barrio Minton et al (2012).…”
Section: Discussionmentioning
confidence: 99%